Fast-Track delle fratture del femore prossimale: inquadramento clinico e strumentale del paziente geriatrico - Gianicola, R.; Ferrara, F.; Antonini, G. (Lo Scalpello - Journal, 2018)
FAST-TRACK IN PROXIMAL FEMUR FRACTURES: CLINICAL AND INSTRUMENTAL ASSESSMENT OF THEGERIATRIC PATIENTThe increase in average population age and, consequently, in fragility fractures demands an innovative approach tothe emerging challenges. A new system of clinical evaluation of the geriatric patient with femoral fracture is presented:multidisciplinary and inspired by the principles of orthogeriatrics, aimed at personalising and optimising thetreatment of this serious disease.